KEMAMPUAN MEMBACA ANAK USIA DINI - Tatu Hilaliyah (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
In the era of globalization has been a very rapid progress in the field of information technology. Progress is demanding support a culture of reading and writing, which is the embodiment of behaviors that includes the ability, habits, interests, and needs to read and write. But until now the culture of reading and writing are not fully developed in the Indonesian society. Therefore, if the Indonesian people to be successful in future development, cultural development is absolutely necessary to read and write. one of the aspects that should be developed in early childhood is the ability to read and write. So the development of the ability to read and write in kindergarten can be implemented as long as the limits of the rules praskolastik and in accordance with the characteristics of the child, ie, to learn while playing and play while learning. Through love reading expected children can read well so as to have a high sense of language, insightful wider diversity and able to develop patterns of creative thinking in him. Providing learning to read in kindergarten age children remain through play for children aged kindergarten play is learning and learning is play.